Clinical and immune responses to anti-CD3 x anti-EGFR bispecific antibody armed activated T cells (EGFR BATs) in pancreatic cancer patients. (1st January 2020) - Lum, Lawrence G.; Thakur, Archana; Choi, Minsig; Deol, Abhinav; Kondadasula, Vidya; Schalk, Dana; Fields, Kristie; Dufrense, Melissa; Philip, Philip; Dyson, Gregory; Aon, Hussein D.; Shields, Anthony F.
ABSTRACT: Purpose This was a phase I/II adoptive T cell trial in 7 locally advanced and metastatic pancreatic cancer patients using 3–8 infusions of anti-CD3 x anti-EGFR bispecific antibody armed activated T cells (BATs) to determine safety, the maximum tolerated dose (MTD), immune responses, time to progression (TTP), and overall survival (OS). Study Design : T cells obtained by apheresis were expanded and armed with EGFRBi, cryopreserved for infusions. In a phase I dose escalation, five patients received three weekly infusions of 10–40 × 10 9 BATs/infusion followed by a booster infusion 3 months later, and 2 patients received 8 infusions twice weekly for 4 weeks in a phase II. The trials were registered at http://www.clinicaltrials.gov, NCT01420874 and NCT02620865. Results : There were no dose-limiting toxicities (DLTs), and the targeted dose of 80 × 10 9 BATs was met. The median TTP is 7 months, and the median OS is 31 months. Two patients had stable disease for 6.5 and 25+ months, and two patients developed complete responses (CRs) after restarting chemotherapy. Infusions of BATs induced anti-pancreatic cancer cytotoxicity, innate immune responses, cytokine responses (IL-12, IP-10), and shifts in CD4 and CD8 Vβ repertoire with enhanced cytoplasmic IFN-γ staining in the Vβ repertoire of the CD8 subset that suggest specific clonal TCR responses. Conclusions : Infusions of BATs are safe, induce endogenous adaptive anti-tumor responses, and may have a potential to improve overall survival.